Lower-limb injury in elite Australian football: A narrative review of kinanthropometric and physical risk factors. (November 2021) - McCaskie, Callum J.; Sim, Marc; Newton, Robert U.; Hart, Nicolas H.
Abstract: Objective: This review aims to provide a succinct and critical analysis of the current physical and mechanical demands of elite Australian football while examining lower-limb injury and the associated physical and kinanthropometric risk factors. Methods: MEDLINE, PubMed, Web of Science and SPORTSDiscus electronic databases were searched for studies that investigated the playing demands, injury trends, and physical and kinanthropometric injury risk factors of elite Australian football. Articles from similar team sports including soccer and rugby (union and league) were also included. Results: While the physical demands of elite AF have steadied over the past decade, injury rates continue to rise with more than two-thirds of all injuries affecting the lower-limbs. Body composition and musculoskeletal morphological assessments are regularly adopted in many sporting settings with current research suggesting high and low body mass are both associated with heightened injury risk. However, more extensive investigations are required to determine whether the proportions of muscle and fat are linked. Repeated assessment of musculoskeletal morphology may also provide further insight into stress fracture rates. Conclusions: While kinanthropometric and physical attributes are highly valued within elite sporting environments, establishing a deeper connection with injury may provide practitioners with more insight into current injury trends. HIGHLIGHTS: Physical demands and injury rates in elite Australian football have remained relatively stable over the last few years. There appears to be an association between body mass and injury. However, their link is not well established. Despite relatively high incidence of stress fractures in AF, routine assessment of hard-tissue has not been undertaken. High-speed running and maximal speed exposure appear to be associated with lower-limb injury in elite AF.